Collection of durum wheat global genetic resources at VIR - Liapounova O. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
This review examines the history of creation and modern condition of the durum wheat collection, its taxonomic and geographic diversity. Problems of plant genetic resources documentation are considered. Description of the passport database structure is given. The paper introduces an intraspecific systematic of T.durum Desf. which was designed in the Department of Wheats, VIR. The main durum breeding centers of Russia and the list of new cultivars are presented.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)